Visual investigation method and structural performance evaluation for DEF induced damaged Indian Railway PC sleepers - Sundaram, Rajamurugan; Matsumoto, Koji; Nagai, Kohei; Awasthi, Anupam (Journal of Asian Concrete Federation, 2018)
Indian Railways uses pre-stressed concrete (PSC) sleepers for its tracks. In the recent years in north and central part of railways, premature cracks were observed in sleepers. Cracks were observed for sleepers 6 to 9 years after their manufacture. In this research, structural performance of damaged sleepers was evaluated in both material and structural level. For material level investigation, core samples were taken from the damaged sleepers. From the cores, reduction in static elastic modulus and compressive strength were bserved for damaged sleepers when compared to undamaged sleepers. For structural level investigation, based on the level of the damage, sleepers were categorized into damaged and undamaged sleepers, and flexural test and shear test for sleepers were conducted. From the bending and shear test results, relationship between the crack pattern and capacity reduction in damaged sleepers was studied. In the flexural test, it was found out that more layers of longitudinal cracks in the central parts reduced its capacity up to 35% when compared to undamaged sleepers. Shear test results showed that it was very close to the minimum requirement for capacity of the sleepers.